2012
DOI: 10.1097/mpg.0b013e318216f2e5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Diagnostic Antibody Tests for Coeliac Disease in Children

Abstract: IgA-EmA and IgA-anti-TG2 tests appear highly accurate to diagnose CD. IgG-anti-DGP tests may help in excluding CD. IgA-AGA and IgA-DGP tests show inferior accuracy. POC tests may achieve high accuracy in the hands of experienced readers, but IgA-anti-TG2/EmA were superior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
170
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(190 citation statements)
references
References 41 publications
6
170
1
13
Order By: Relevance
“…The presence of anti-TG2 antibodies in serum represents a CD marker [4]. However, intestinal anti-TG2 antibodies may be even more relevant from a clinical viewpoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of anti-TG2 antibodies in serum represents a CD marker [4]. However, intestinal anti-TG2 antibodies may be even more relevant from a clinical viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that, as well as a spectrum of clinical presentations, there is a wide spectrum of alterations of the jejunal histology, ranging from an infiltrative lesion to villous atrophy [3]. Gluten is able to induce the production of autoantibodies that can be found in the serum of CD patients and that have, from a diagnostic viewpoint, a very high sensitivity and specificity [4]. These autoantibodies recognize an endomysial antigen known today as transglutaminase 2 (TG2) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Its characteristics include a variable clinical picture, the presence of specific antibodies of the DQ2 and DQ8 haplotype, and enteropathy [1]. Currently, the antibodies used for serological diagnostics of celiac disease are antibodies against tissue transglutaminase, deamidated gliadin peptides and the endomysium of the smooth muscles of the gastrointestinal tract [2]. The basis for a diagnosis of celiac disease is confirmation of histopathological lesions type 2 or 3, according to the Marsh classification as modified by Oberhuber, i.e.…”
mentioning
confidence: 99%
“…It has been suggested that about 20-30% of celiac disease pediatric patients could be diagnosed based solely on high levels of tTGA without the need for an invasive endoscopic procedure [3]. Current guidelines suggest that a tTGA level 10 times over the cut-off level of positivity could be optimal for omitting of duodenal biopsies in celiac disease diagnosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of disease specific autoantibodies and associated genetic markers over the past decades [3], the intestinal biopsy has been questioned as the current golden standard of methods for celiac disease diagnosis [4]. Recently, serology and HLA risk genotypes have been suggested to suffice in the diagnosis of cases with clear symptoms and high tissue transglutaminase autoantibody (tTGA) levels [5].…”
Section: Introductionmentioning
confidence: 99%